A court decision in cases of administrative jurisdiction: spectral analysis of debatable aspects of its essence and legal nature - Розум, Ігор Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article a comprehensive analysis of debatable theoretical aspects of doctrinal approaches to determine the essence and legal nature of a court decision in cases of administrative jurisdiction have been made, constitutive features of its substance have been distinguished, and based on the mentioned above the author’s own definition of this concept has been suggested. On the basis of the research and generalization of the current administrative-procedural legislation and judicial practice of proceedings in administrative cases an integral system of requirements to the court decision of an administrative court have been outlined.